2023
DOI: 10.1007/s00432-023-05465-9
|View full text |Cite
|
Sign up to set email alerts
|

Emerging markers of cancer cachexia and their relationship to sarcopenia

Melanie Lipshitz,
J. Visser,
R. Anderson
et al.

Abstract: Purpose Emerging biomarkers of cancer cachexia and their roles in sarcopenia and prognosis are poorly understood. Baseline assessments of anthropometrics, sarcopenia, cachexia status and biomarkers of cachexia were measured in patients with advanced cancer and healthy controls. Thereafter, relationships of the biomarkers with cachexia and sarcopenia were explored. Methods A prospective case–control design was used, including 40 patients with advanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 58 publications
1
5
2
Order By: Relevance
“…In contrast to other studies, that showed more than a threefold increase of serum CXCL5 concentrations in cancer [ 17 ], the current study found no difference for cases vs. controls for CXCL5 ( p = 0.22) [ 19 ]. Studies that report raised CXCL5 levels may be questionable due to inconsistencies in CXCL5 measurement, differing primary diagnoses [ 17 ] and the degree of metastatic spread [ 35 ], factors that may have influenced CXCL5 results in the study by Lipshitz et al [ 19 ].…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…In contrast to other studies, that showed more than a threefold increase of serum CXCL5 concentrations in cancer [ 17 ], the current study found no difference for cases vs. controls for CXCL5 ( p = 0.22) [ 19 ]. Studies that report raised CXCL5 levels may be questionable due to inconsistencies in CXCL5 measurement, differing primary diagnoses [ 17 ] and the degree of metastatic spread [ 35 ], factors that may have influenced CXCL5 results in the study by Lipshitz et al [ 19 ].…”
Section: Discussioncontrasting
confidence: 99%
“…As described previously [ 19 ], measurement of systemic biomarker concentrations revealed statistically significant increases ( p < 0.05) in all of the following biomarkers in the group of cancer patients relative to controls: blood platelets, NLR, PLR, SII, CRP, IL-6, IL-8, and TNFα. Concentrations of biomarkers that were significantly decreased ( p < 0.05) in the cohort of cancer patients included albumin, Hb, and lymphocyte count, while white blood cell counts (WBCs), neutrophil counts, and concentrations of CXCL5 and H3Cit were comparable between patients and controls.…”
Section: Resultssupporting
confidence: 74%
See 3 more Smart Citations